Design of Rf Power Amplifier for aDual-Purpose Communication Satellite - Umar, S.; Onuh, S.; David, E.; Adesina, L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper focuses on the design of RF power amplifiers for a dual-purpose communication satellite. The rapid growth in the use of power amplifiers for satellite communication is been documented. One of the major part of a high frequency communication system is the power amplifiers which amplifiers signals above 3GHz, into a frequency in the order of millions of cycles. The design of a radio frequency power amplifier is the most obvious solution to overcoming the battery lifetime limitation in the satellite communication system. This paper focuses on the design of a radio frequency amplifier with a technique to improve the drain efficiency of the class-F amplifier. This technique uses two passive networks; one of them is in series with the shunt capacitor Cs and the other in series with the MOSFET transistor’s source terminal. The technique shows a significant improvement in the drain efficiency, which increases from 62% to 90%. This results to the demand for compact, low cost, and low power RF amplifiers. Thus, the design consideration was implemented, recorded, tested and met design specification.